(3GdeYGjjQ GdGSGSjI ddYedjI GdGQTGOjI GdfaSjI GdQjGVjI GdeSGYOI Ydi GdJahb GdQjGVj (B: (3OQGSI MGdI daQjb GdeUGQYI QGS GdhGO HQL HhYQjQjL s - (3Hf GdfhQ , eUHGMs; (3Hf Ycj, eMfO Bcdjs; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2021)
(3Gf GdgOa ef GdOQGSI gh GdJYQa Ydi GdeYGjjQ GdCSGSjI ddYedjI GdEQTGOjI GdfaSjI GdQjGVjI GdeSGYOI Ydi GdJahb GdQjGVj, MjK GYJeO GdHGMK aj gPg GdOQGSI Ydi GdefgL GdhUaj GdJMdjdj, hGSJNOGe OQGSI GdMGdI cCOGI dOQGSI XGgQI Jahb QjGVjj aQjb GdeUGQYI (B"(3Ced QCS GdhGO(B"(3, hJchfJ YjfI GdOQGSI ef(B(15) (3eUGQYG eJahbG efge (B(11) (3ef Ufa GdCcGHQh (B(04) (3ef Ufa GdChGSW ddehSe GdQjGVj(B(2019-2020) (3hbO Je GNJjGQge ef CaQGO GdeLJeY GdCUdj ddOQGSI fXQG dJahbge aj eNJda GdHWhdGJ GdhWfjI hGdOhdjI(B. (3MjK bOe GdHGMK ebjGS GdSdhc GdJfGaSj deMeO MSf YdGhj ddeUGQYjf HZQV aMU GdaQVjI GdChdi h GSJeGQI ESJHjGf daMU GdaQVjGJ GdKdGKI GdeJHbjI, hJhUd GdHGMK ef NdGd GdOQGSI GdejOGfjI Edi Cf Sdhc GdeUGQYjf GdeJahbjf jeJGR HGdcaGM h GdfVGd ef CLd GdahR eeG SGYO Ydi Jahb gDdGA GdeUGQYjf h HdhZge eSJhjGJ YGdjI ef GdCOGA NdGd eThGQge GdQjGVj, hef LgI CNQi JeJY gDdGA GdeUGQYhf HMQjI JbQjQ GdeUjQ NdGd eThGQge GdQjGVj h HeQGabI EQTGOjI eSJeQI SGgeJ ajgG HYV eDSSGJ GdJfTFI GdGLJeGYjI JMJ ETQGa GdeOQH QZe JbUjQ EOGQI GdfGOj h EZaGdgG dOhQgG GdEQTGOj ef hLgI fXQ GdeUGQYjf , ceG Cf EgJeGe hJYdb GdeUGQYjf GdeJahbjf HJYGdje GdOjf GdESdGej bO SGYOge aj GdJQcjR h GdGSJYOGO ddefGaSGJ, hGJNGP bQGQGJge GdeUjQjIs
(3OcJhQGgs
Keywords: (3GdGQTGO GdfaSjs; (3GdEQTGO GdfaSj G dQjGVjs; (3GdJahb GdQjGVjs